Modelling the scaling up of sustainable farming into Agroecology Territories: Potentials and bottlenecks at the landscape level in a Mediterranean case study. (1st December 2020) - Padró, R.; Tello, E.; Marco, I.; Olarieta, J.R.; Grasa, M.M.; Font, C.
Abstract: There is a need for a socioecological transition towards sustainable agri-food systems that recover the organic functioning and the closure of socio-metabolic cycles at the lower feasible scales. This implies an agroecology leap forward aimed at scaling up eco-functional intensification practices from the plot to the landscape level, and identifying synergies and trade offs involved in these jump of scale. We present a new methodology to devise feasible, viable and desirable prospective horizons of agroecology landscapes to inform deliberative processes for decision-making: A Sustainable Agroecological Farm Reproductive Analysis (SAFRA). The model is based on biophysical fund-flow integrated and reproductive accounting of the Agrarian Metabolism, which allows to identify the optimal configuration of land uses, livestock densities, diets and the amount of sustainable population to maximize any given societal objective. The results of this SAFRA modelling, run for a Mediterranean case study, identify the potentials of that scaling up processes towards agroecology territories by means of eco-functional intensification practices addressed to the closure of the yield gap with industrial agriculture. These results challenge the concept of sustainability under the current socioecological functioning of nutrient cycles, and help to devise a potential transitionary near-to-sustainable horizon by using the soil nutrients stock, something easily applicable in over-fertilised western agricultural soils as a feasible first step in the socio-ecological transition. Finally, the results also show that shifting from current diets towards local healthy diets would maximize the synergies among the agroecosystem components (livestock, crops, forests, pastures, farmers and society) by recovering complex agro-silvo-pastoral mosaics that have the potential to increase up to 125% the joint organic yields. Highlights: SAFRA calculates prospective agroecology territories for social deliberation. Upscaling agroecology at landscape level may close yield gaps with industrial farming. Current sewage sludge flows should be recovered to allow sustainable farm systems. A local healthy diet could require an area 2.2 times lower than for a current diet.